Imperatorin ameliorates lipopolysaccharide induced memory deficit by mitigating proinflammatory cytokines, oxidative stress and modulating brain-derived neurotropic factor. (October 2018) - Chowdhury, Amrita A.; Gawali, Nitin B.; Shinde, Prashant; Munshi, Renuka; Juvekar, Archana R.
Graphical abstract: Highlights: IMP reversed the LPS induced memory deficit in MWM and Y-maze. IMP attenuated oxidative stress and diminished acetylcholinesterase activity. IMP restored the BDNF levels and reversed the increase in TNF-α and IL-6. IMP demonstrated neuroprotective potential in LPS induced memory deficit. Abstract: Background: Lipopolysaccharide (LPS), an endotoxin from the outer membrane of Gram negative bacteria has been reported to cause neuroinflammation and learning and memory deficits. There are reports describing the beneficial effects of Imperatorin (IMP), a naturally occurring furanocoumarin in central nervous system (CNS) disorders such as anxiety and epilepsy. Objective: In the current study, we investigated whether IMP protects against LPS mediated memory deficits and neuroinflammation. Methods: Mice pretreated with IMP (5, 10 mg/kg po ) were administered LPS (250 μg/kg ip ) for 7 days. Memory was evaluated in the Morris water maze (MWM) and Y maze. The mice were euthanised and different biochemical assessments were carried out to measure oxidative stress and acetyl choline esterase (AChE). Further, evaluation of proinflammatory cytokines such as tumor necrosis factor (TNF-α) and interleukin-6 (IL-6) levels and brain derived neurotrophic factor (BDNF) in hippocampus and cortex of brain were performed. Results: LPS administration caused poor memory retention in both, MWM and Y maze, and caused distinct oxidative stress since decrease in superoxide dismutase (SOD), reduced glutathione (GSH) levels and increased lipid peroxidation were observed. Also, a significant rise was observed in the levels of AChE. Moreover, a rise in TNF-α and IL-6 levels and depleted levels of BDNF were noted. IMP pretreatment reversed LPS induced behavioral and memory disturbances and significantly decreased the oxidative stress and AChE levels. It also reduced TNF-α and IL-6 levels and caused a significant upregulation of BDNF levels. Conclusion: Present study highlights the potential neuroprotective role of IMP against LPS mediated cognitive impairment and neuroinflammation.